Diversity and feeding guilds of understorey bird in an oil palm plantation and adjacent Peat Swamp forest in Betong Division, Sarawak, Malaysia - Bettycopa, Amit (Universiti Malaysia Sarawak, (UNIMAS), 2015)
One of the biggest concerns regarding the conversion of tropical forest into oil palm plantation is the expansion of plantation into peatland and the impact it has on species diversity. This study is important to confirm what has been reported for oil palm on minerals soils that bird diversity is reduced in oil palm plantation and no studies of similar nature have been conducted on peatland in Sarawak. The first objective of this study is to document the species diversity of understorey bird in oil palm plantation planted on peat and adjacent peat swamp forest in Betong Division, Sarawak. A total of 48 species were captured using mist-nets over a period of 34 days of which 30 species were recorded in oil palm plantation and 31 species were recorded in adjacent peat swamp forest. The 48 species of bird recorded in this study were further categorized into forest bird and garden bird. Forest bird species are reduced in number as we move from inside the peat swamp forest into oil palm plantation while garden birds were present only in oil palm plantation. The total species and number of individuals of garden birds increased from boundary towards the centre of the oil palm plantation. The second objective was to determine the direction and frequency of bird crossing between oil palm plantation and adjacent peat swamp forest. Results showed that there were significantly more birds hitting the boundary nets from the oil palm plantation side. A significantly higher frequency of bird crossed the boundary site in the morning compared to midday and late afternoon, presumably for foraging purpose. Finally, the third objective of the study was to determine the reason behind Pycnonotus goiavier abundance in oil palm plantation hence a study on their dietary habits was conducted. Pycnonotus goiavier was found to actively select insects from the Order Coleoptera as its main food in oil palm plantation, followed by Homoptera, Diptera, Hemiptera and Hymenoptera. However, this bird completely avoids feeding on insects from Order Odonata, Orthoptera, Dictyoptera and Lepidoptera. Hence, oil palm habitat is providing ample food resources such as insect for this bird species to continue their survival. This study showed that understorey bird species diversity is significantly lower in oil palm plantation than in adjacent peat swamp forest and this finding supported what has been reported for oil palm on minerals soils. Therefore, plantation management should include conservation efforts for the birds both within and in surrounding oil palm areas in order to create biodiversity-friendly plantations besides increasing oil palm yield.